Homeric and/or hymns: some fifteenth-century approaches - Thomas, O. (Oxford University Press, 2016)
Discusses the manuscripts of the Homeric Hymns as evidence for how they were read in the fifteenth century, and particular allusions made to them in the works of Francesco Filelfo and Michael Marullus.